Profesi Akuntan di Era Society 5.0 - Miranti Handayani (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2023)
After the Covid - 19 pandemic, there was a change in the behavior of all humans in the use of technology in every activity, including in the accounting sector. This is known as the Society 5.0 era, where smart robots and machines now take on the role of accountants. The purpose of this study is to find out how the accounting profession deals with digital accounting in the Society 5.0 era. The research method used is a qualitative approach with data collection methods, literature studies and literature studies. The results of this study indicate that the role of the accounting profession has shifted from the era before Society 5.0. But this will not result in the disappearance of the accounting profession in the future. Therefore, an accountant is required to have skills in technology in order to survive in the era of Society 5.0 and the next era